CUSTOMARY SANCTIONS FOR NON-PRAYING INDIVIDUALS IN LIMA PULUH KOTA: A SADD AL-DZARIAH PERSPECTIVE ON STRENGTHENING SOCIAL NORMS - Desembri, Desembri; Busyro, Busyro; Ikhwan, Ikhwan (Al Ushuliy: Jurnal Mahasiswa Syariah dan Hukum, 2024)
This article examines the implementation and impact of social sanctions imposed on deceased individuals who did not perform prayers in Nagari Andaleh, Lima Puluh Kota Regency. In Islam, performing funeral prayers is a collective obligation for Muslims. However, in Nagari Andaleh, a unique policy is practiced: funeral prayers are withheld for those who never observed daily prayers during their lives. This practice is rooted in the local interpretation of Islamic teachings. Using the Sadd al-Dzariah approach, this study explores how these sanctions influence religious awareness and social cohesion within the community. Employing an ethnographic research method, the study integrates field observations, in-depth interviews, documentation, and juridical and sociological analyses. The findings reveal that these sanctions act as both informal law enforcement and a strategic effort to reinforce religious values and collective consciousness. The article provides an in-depth analysis of the social, psychological, and spiritual implications of this policy, offering valuable insights into the evolving interplay between religion, culture, and community identity in Nagari Andaleh. This study not only highlights the local community's innovative approach to addressing religious obligations but also sheds light on its broader impact on shaping behavior and sustaining religious norms.